Music Calling for Social Transformation: Some Reflections on Poulenc's Surrealist Work Le Bal Masqué - Marisi Rossella (Sciendo, 2019)
Grounding on Marx's and Freud's theories, Surrealists sought the liberation of the individual and the transformation of society. With this aim they brought together usual objects in unusual combinations, surprising the audience and giving them the opportunity to perceive reality with different eyes. This study reflects on a character of Jacob's and Poulenc's Le bal masqué, Mademoiselle Malvina, presented as epitome of the bourgeoisie and described in both text and music as duplicitous and superficial.